Acesso vs propriedade: estudo sobre os fatores que influenciam a adesão do consumidor por novos modelos de negócio na indústria de linha branca - Nardocci , Thiago Ferreira (2021)
This study investigates the consumer´s perception of a product-service system offer as a replacement of the ownership of an automatic washing machine. The theme was approached from a theoretical review of shared economics, which sets the background in which product service systems are gaining relevance. It also contemplates the types of product-service systems (PSS), trends that affect the shared economy and consumer behavior. Since it is a recent phenomenon with little knowledge produced, a study with a qualitative methodology was elaborated through content analysis of focus groups and semi-structured interviews.